2003
DOI: 10.1016/j.ijgo.2003.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum fetal pulse oximetry and fetal heart rate decelerations

Abstract: Modifications in FHR occur simultaneously with alterations in FSpO(2), although the latter do not persist in time. Different degrees of FSpO(2) seen prior to deceleration are an expression of fetal respiratory status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Puertas and colleagues designed a study to determine the behaviour of FSpO 2 during different patterns of FHR decelerations 6 . Additionally, for each deceleration analysed, they measured FSpO 2 at different instants of deceleration (2 and 1 min before the onset of deceleration, during progressive deceleration, maximum decrease, during recovery, 1 and 2 min after recovery of the deceleration).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Puertas and colleagues designed a study to determine the behaviour of FSpO 2 during different patterns of FHR decelerations 6 . Additionally, for each deceleration analysed, they measured FSpO 2 at different instants of deceleration (2 and 1 min before the onset of deceleration, during progressive deceleration, maximum decrease, during recovery, 1 and 2 min after recovery of the deceleration).…”
Section: Discussionmentioning
confidence: 99%
“…2,30 Puertas and colleagues designed a study to determine the behaviour of FSpO2 during different patterns of FHR decelerations. 6 Additionally, for each deceleration analysed, they measured FSpO2 at different instants of deceleration (2 and 1 min before the onset of deceleration, during progressive deceleration, maximum decrease, during recovery, 1 and 2 min after recovery of the deceleration). They found that fetal oxygen saturation during the course of labor decreased significantly in parallel with the maximum decrease in decelerations and during recovery of heart rate, in all groups of decelerations they studied (early, variable, late, prolonged).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is likely that more than one pathophysiologic event may be involved in vivo in the genesis of the majority of decelerations. Several reports have suggested that the most ominous variants are decelerations lasting for more than 5 minutes, irrespective of the type [18,19].…”
Section: Introductionmentioning
confidence: 99%